1992
DOI: 10.1302/0301-620x.74b5.1527127
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular morphine for pain relief after knee arthroscopy

Abstract: We performed a randomised double-blind controlled study in patients undergoing elective knee arthroscopy to assess the effect of intra-articular morphine on postoperative pain relief. Patients in the study group (n = 10) received 5 mg of morphine in a 25 ml dilution intra-articularly while those in the control group (n = 10) received 25 ml of saline. Postoperative pain was assessed at intervals by a visual analogue scale and the requirement for supplementary analgesia was recorded. Those in the study group had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
58
0
8

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(75 citation statements)
references
References 0 publications
6
58
0
8
Order By: Relevance
“…Stein et al showed that low doses of intra-articular morphine (standard formulation) reduced pain after knee surgery by an action specific to local intra-articular receptors [ 11; consumption of supplemental postoperative analgesics was also shown to be significantly reduced. These findings were confirmed by Joshi et al [2]. However, in a more recent study, Raja et al found no evidence for the peripheral action of morphine, paradoxically finding that it was associated with higher pain scores than saline or bupivacaine during the first 2 h following arthroscopy [3].…”
mentioning
confidence: 81%
“…Stein et al showed that low doses of intra-articular morphine (standard formulation) reduced pain after knee surgery by an action specific to local intra-articular receptors [ 11; consumption of supplemental postoperative analgesics was also shown to be significantly reduced. These findings were confirmed by Joshi et al [2]. However, in a more recent study, Raja et al found no evidence for the peripheral action of morphine, paradoxically finding that it was associated with higher pain scores than saline or bupivacaine during the first 2 h following arthroscopy [3].…”
mentioning
confidence: 81%
“…This may explain why some studies with regional or local anaesthesia have failed to show the effect of IA morphine, (29)(30)(31) whereas patients operated under general anaesthesia have demonstrated profound effect of IA morphine. (4,15,32,33) In the current study, spinal anasthesia with bupivacaine was applied. No use of local anaesthetics into the intraarticular space eliminates its possible negative effect on morphine analgesia in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In four studies, IA morphine 5 mg in 25 ml of saline resulted in a significant reduction in postoperative pain for up to 24 h after various arthroscopic procedures [4,5] and after anterior cruciate ligament repair [6,7]. In none of these studies was a control for systemic effects of the locally administered morphine included .…”
Section: Discussionmentioning
confidence: 99%
“…Pre-oxygenation replaces alveolar nitrogen with oxygen, ing systems [ 1-31, Four maximal deep breaths with a circle allowing a much longer period before hypoxaemia occurs breathing system produce a comparable degree of preduring the apnoeic period following induction of anaesoxygenation [4,5] when arterial oxygen tension or end-tidal thesia. Many studies since the 1950s have demonstrated oxygen concentration has been measured.…”
Section: Discussionmentioning
confidence: 99%